Prognostic significance of YKL-40 expression in canine cutaneous mast cell tumors - Chien-Chun Kuo; Wei-Hsiang Huang; Su-Ya Yang; Yen-Chen Chang; Hui-Wen Chang; Chian-Ren Jeng; Jih-Jong Lee; Albert Taiching Liao (BMC Veterinary Research)
Abstract Background YKL-40, a secretory glycoprotein, is involved in tumor cell proliferation, metastasis, and angiogenesis in human cancers. Its overexpression has been correlated with unfavorable prognosis in many human cancers. In veterinary medicine, elevated YKL-40 levels in the serum of canine cutaneous mast cell tumors (cMCTs) were observed in our previous study. However, the expression pattern of YKL-40 in canine cMCT tissues, along with its association with clinical and pathological features, is still unknown. This study aims to retrospectively investigate the expression level of YKL-40 in the tissues of canine cMCTs and its correlation with clinical features, pathological characteristics, and clinical outcomes. Forty formalin-fixed paraffin-embedded cMCT tissues collected from forty dogs were diagnosed as low-grade (n = 20) or high-grade s(n = 20) MCT according to the Kiupel grading system. The expression level of YKL-40 in cMCT tissues was investigated using immunohistochemical staining and immunoreactivity score (IRS). Results YKL-40 was expressed in all cMCTs at different levels, with significantly stronger expression in low-grade cMCTs compared to high-grade cMCTs. The expression level was also associated with tumor diameter, histological grade, mitotic counts, vessel density, and survival of cMCTs. The overall survival of cMCT dogs showed significant differences (p < 0.01) among mild (n = 15, MST 219 days), moderate (n = 19, MST not reached), and high (n = 6, MST not reached) YKL-40 expression groups. Among low-grade cMCTs, overall survival was significantly different between mild YKL-40 expression (MST 319 days) and moderate to high YKL-40 (MST not reached) expression (p < 0.01). In high-grade cMCTs, overall survival was not correlated with YKL-40 expression (p = 0.6589). Conclusions This study found that the YKL-40 expression level was significantly stronger in low-grade than in high-grade canine cutaneous mast cell tumors and was associated with various clinical and pathological features. Stronger YKL-40 expression level correlated with longer survival time, especially in low-grade cMCTs. Therefore, YKL-40 could serve as a prognostic marker for cMCTs.